If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x-5)=3(2x-8)
We move all terms to the left:
(2x-5)-(3(2x-8))=0
We get rid of parentheses
2x-(3(2x-8))-5=0
We calculate terms in parentheses: -(3(2x-8)), so:We get rid of parentheses
3(2x-8)
We multiply parentheses
6x-24
Back to the equation:
-(6x-24)
2x-6x+24-5=0
We add all the numbers together, and all the variables
-4x+19=0
We move all terms containing x to the left, all other terms to the right
-4x=-19
x=-19/-4
x=4+3/4
| -4z-10=10-8z | | -7-6u=-5u | | 6b-10=3b-1 | | 9p=10p+3 | | 5y–14=21 | | -g+7=-9+g | | £^(2z-1)=1 | | 6d+6=7d | | 10^(x+2)=650 | | -z=9z−10 | | 3D-24=2d | | –z=9z−10 | | 5e+10=8e-5 | | 3b=4+2b | | -3(w+1)=3w+45 | | 2(u+5)-5u=-8 | | 5x+1≤=3x-17 | | X2-20x+50=0 | | 2r2-3=125 | | 7/x-3=0 | | W=4.5/2w | | W=4.5/(2w) | | -3x^2-20x+1600=0 | | 5-35x+2=47-3x+1 | | -4(x+4)=4(x+4) | | 18=x+50-x+32 | | 33+x=3x-28 | | 3x-30+21=33 | | 3x-28+21=33 | | 3x-28=21 | | 3x-30+33=3x-28 | | 33=3x-28 |